The effects of GSK2981710, a medium‐chain triglyceride, on cognitive function in healthy older participants: A randomised, placebo‐controlled study. (23rd May 2019) - O'Neill, Barry V.; Dodds, Chris M.; Miller, Sam R.; Gupta, Ashutosh; Lawrence, Philip; Bullman, Jonathan; Chen, Chao; Dewit, Odile; Kumar, Subramanya; Dustagheer, Mushi; Price, Jeffrey; Shabbir, Shaila; et al.
Abstract: Objective: This double‐blind, randomised, placebo‐controlled, two‐part study assessed the impact of GSK2981710, a medium‐chain triglyceride (MCT) that liberates ketone bodies, on cognitive function, safety, and tolerability in healthy older adults. Methods: Part 1 was a four‐period dose‐selection study ( n  = 8 complete). Part 2 was a two‐period crossover study ( n  = 80 complete) assessing the acute (Day 1) and prolonged (Day 15) effects of GSK2981710 on cognition and memory‐related neuronal activity. Safety and tolerability of MCT supplementation were monitored in both parts of the study. Results: The most common adverse event was diarrhoea (100% and 75% of participants in Parts 1 and 2, respectively). Most adverse events were mild to moderate, and 11% participants were withdrawn due to one or more adverse events. Although GSK2981710 (30 g/day) resulted in increased peak plasma β‐hydroxybutyrate (BHB) concentrations, no significant improvements in cognitive function or memory‐related neuronal activity were observed. Conclusion: Over a duration of 14 days, increasing plasma BHB levels with daily administration of GSK2981710 had no effects on neuronal activity or cognitive function. This result indicates that modulating plasma ketone levels with GSK2981710 may be ineffective in improving cognitive function in healthy older adults, or the lack of observed effect could be related to several factors including study population, plasma BHB concentrations, MCT composition, or treatment duration.